Prevalence and associated risk factors of mycobacterial infections in slaughter pigs from Mubende district in Uganda - Muwonge, Adrian; Kankya, Clovice; Godfroid, Jacques; Djonne, Berit; Opuda-Asibo, John; Biffa, Demelash; Ayanaw, Takele; Munyeme, Musso; Skjerve, Eystein (Tropical animal health and production, 2010)
To date, the public health relevance of mycobacterial infections in pigs is not well investigated despite high risk of infection. Recently, there has been a documented increase in opportunistic infections and risk of acquiring opportunistic mycobacterial infections in HIV/AIDS patients in Mubende district; unfortunately, there has been no published information on the epidemiology of mycobacterial infections in this area. This study was carried out between September 2008 and February 2009. Investigations were done to assess the prevalence and associated risk factors of mycobacterial infections in slaughtered pigs in Mubende district of Uganda. A total of 997 pigs (53.7% male and 46.3% female) from 31 different slaughterhouses were examined for the presence of lesions compatible with TB and mycobacterial infections. Pathologic tissue specimens were collected for culturing and isolation of mycobacteria.
Keywords: Mycobacteria; Pigs; Risk factor; Uganda